PROSPECTS FOR OPTIMIZING THE STRUCTURE OF IMPORTS OF GOODS IN THE REPUBLIC OF UZBEKISTAN - Shadmankulov Anvar Ablakulovich,; Najmiddinov Dilshod Fakhriddinovich,; Uzokov Oybek Amirulla ugli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article reveals the formation and peculiarities of international trade and economic relations in the process of integration of the economy of the Republic of Uzbekistan into the world capital market. Conceptual approaches to expanding foreign economic cooperation of the Republic of Uzbekistan with the leading CIS and regional countries and the EEU, SCO organizations, as well as international financial institutions, leading foreign companies and banks are presented. The effectiveness of the implementation of the Action Strategy on the five priority areas of development of the Republic of Uzbekistan for 2017-2021 is highlighted.